Perioperative changes in cardiac biomarkers in juvenile cats during neutering - Konishi, Keisuke; Sakamoto, Mei; Satake, Chikara; Isaka, Mitsuhiro; Okazaki, Seiji; Kono, Shota; Nakamura, Takayuki; Tashiro, Hideki; Ushigusa, Takahiro (Frontiers in Veterinary Science, 2022)
Perioperative myocardial injury (PMI) is commonly caused by myocardial ischemia that develops during or after non-cardiac surgery. It occurs in 17.9% of human patients after non-cardiac surgery due to elevated high-sensitive cardiac troponin at perioperation. However, PMI has not been demonstrated in cats. To investigate its occurrence, this study aimed to analyze the perioperative changes in cardiac biomarkers and clinical data, including measurement of vital signs, echocardiography, blood pressure, electrocardiogram, X-ray, and anesthetic profile, in 30 juvenile cats under neutering surgery. All cats had increased high-sensitive cardiac troponin I (hs-cTnI) postsurgery compared with presurgery. In particular, 48% of cats (14/29) showed elevated hs-cTnI over reference range after surgery. In all groups, hs-cTnI and systolic arterial blood pressure (SAP) were significantly higher at 0 h and 18 h postoperation than at preoperation. A significant positive correlation was found between hs-cTnI and SAP at 18 h postoperation. Atrial natriuretic peptides, heart rate, and left ventricular wall thickness were markedly higher at 0 h postoperation than at preoperation; however, respiratory rate and body temperature were significantly lower at 0 h postoperation than at preoperation. Anesthetic time and hs-cTnI were significantly higher at 18 h postoperation in females than in males. Significant positive correlations were observed between hs-cTnI and anesthetic time at 18 h postoperation in females. These results indicate that postoperative hs-cTnI level can greatly increase in juvenile cats and hs-cTnI measurement at perioperation is potentially beneficial for early detection and evaluation of the presence of PMI.